2004
DOI: 10.1074/jbc.m401343200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Induces Collagenase-3 (MMP-13) Expression in MC3T3-E1 Osteoblastic Cells

Abstract: Mechanical strain plays a crucial role in bone remodeling during growth and development and healing of bone besides systemic and local factors. One of the major factors involves in remodeling process is matrix metalloproteinases (MMPs) such as MMP-13 that has been shown to degrade the native interstitial collagens in several tissues. To study how mechanical strain affects extracellular matrix degradation by MMP-13, a biaxial strain was applied to MC3T3-E1 osteoblastic cells plated onto a collagen-coated flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 52 publications
5
84
3
Order By: Relevance
“…It has long been known to occur in endothelial cells, where not only ERK1/2 kinase, but also p38, BMK-1 and JNK are activated (Yan et al, 1999). In bone cells many groups have shown activation of ERK1/2 in particular (You et al, 2001;Jessop et al, 2002;Weyts et al, 2002;Yang et al, 2004;Plotkin et al, 2005).…”
Section: Mapk Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been known to occur in endothelial cells, where not only ERK1/2 kinase, but also p38, BMK-1 and JNK are activated (Yan et al, 1999). In bone cells many groups have shown activation of ERK1/2 in particular (You et al, 2001;Jessop et al, 2002;Weyts et al, 2002;Yang et al, 2004;Plotkin et al, 2005).…”
Section: Mapk Signalingmentioning
confidence: 99%
“…As a result of increased eNOS expression, nitric oxide (NO) synthesis is enhanced. ERK1/2 activation by mechanical stress has been linked to other specific genes such as strain induction of collagenase-3 (Yang et al, 2004), as well as to proliferation (Boutahar et al, 2004). Both fosB and its spliced variant, deltafosB, which has been shown to stimulate increases in bone density in vivo, are induced by mechanical loading in mouse hind limb bone and by fluid shear stress in mouse calvarial osteoblasts (Inoue et al, 2004).…”
Section: Mapk Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous molecular evidences indicated that DDR2 signaling can directly up-regulate the transcription of MMP-13 [21], a protein that is abundantly expressed by MC3T3-E1 cells [23]. Thus, MMP-13 was chosen as a molecular marker to evaluate the consequence of Cbl-b knockdown on DDR2 downstream events.…”
Section: Cbl-b Overexpression Decreases the Protein Stability Of Ddr2mentioning
confidence: 99%
“…Moreover, it was found that many tumours are characterised by the formation of fibrotic tissue (Brewster et al 1990, Johnson 2001, Pujuguet et al 1996 or by degradation of ECM due to excessive production of MMP-13 (Yang 2004). Johnson (2001) argued that the formation of fibrosis can be due to several probably concurring reasons: increased de novo synthesis of ECM proteins, decreased activity of its degrading enzyme (MMP), and upregulation of the tissuespecific inhibitors of metalloproteinases (TIMP), that is, the molecules that make matrix degrading enzymes (MDEs) ineffective.…”
Section: Introductionmentioning
confidence: 99%